International Nursing: Job Satisfaction Among Critical Care Nurses in a Governmental Hospital in Saudi Arabia. Issue 3 (July 2018) - Mari, Mohammad; Alloubani, Aladeen; Alzaatreh, Mohammad; Abunab, Hamzeh; Gonzales, Analita; Almatari, Mohammad
Abstract : Job satisfaction improves the outcome of health care services. Nurses' job satisfaction should receive more attention in Saudi Arabia, and worldwide. This study was undertaken to measure factors that affect job satisfaction among critical care nurses at King Khalid Hospital in Saudi Arabia. This study used a quantitative, cross-sectional method. A convenient sample of 190 critical care nurses was recruited from the main government hospital in Saudi Arabia. Job satisfaction scales were used in this study. Overall, the staff nurses were neither satisfied nor dissatisfied with their work. The majority of participating nurses were moderately satisfied with their relationships with coworkers (mean = 4.24, standard deviation [SD] = 1.66) and nature of their jobs (mean = 4.13, SD = 0.74). Their lowest satisfaction scores were related to communication (mean = 3.42, SD = 0.82), followed by pay (mean = 3.7, SD = 0.65), and supervision (mean = 3.75, SD = 0.55). Job satisfaction of staff nurses is marginal. This calls for leadership intervention. Decision-makers must consider this when adopting new policies to enhance nurses' job satisfaction.